Distance Education in Education System of India : A Study: Exploring the Benefits and Implications of Distance Education in India Education System (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Distance Education is one of the most recent educational trends, supporting a large number ofcompetitors in achieving their goals with the least amount of effort. By coming to their doorsteps, distanceeducation is making the lives of many up-and-comers easier. The open education framework is supportingin the country's proficiency expansion. For the new generation of working professionals, distance learninghas become a common tool. People who have faith in their ability to multitask have a massive day plan.They try to juggle a plethora of errands and manage their time. Distance education in India is a wiseinvestment in terms of not only conserving time but also getting the best skills and information aboutyour work force. Distance learning provides access to study programmes that would otherwise beunavailable to understudies in their local area. It's also achievable, and it lends a lot of credibility toyour educational marvel. Distance learning incorporates a shifting scope of demonstrating methods,making it enticing, exceptional, and understudy driven. Employee boards originate from variousfoundations, ensuring that the understudies are given globally appreciated and confirmed information.The Indian government is also promoting distant learning by creating open universities around thecountry with the goal of educating the populace. Education and training in important professional areas,as well as the development and management of huge communication networks, are all part of theactivity. Open universities have proven to be an important and innovative component of highereducation in many countries, and they are seen as a critical instrument of human resource developmentby educational planners and policymakers, as well as the general public